A Bibliometric Review of the Keap1/Nrf2 Pathway and its Related Antioxidant Compounds - Ana Paunkov; Dionysios V. Chartoumpekis; Panos G. Ziros; Gerasimos P. Sykiotis (Antioxidants, 2019)
Nrf2 is a master transcriptional regulator of antioxidant and cytoprotective pathways. Currently in its third decade, research on Nrf2 has expanded to encompass not only basic but also clinical studies. In the present bibliometric review, we employed the VOSviewer tool to describe the existing Nrf2 literature landscape. As of July 2019, 11,931 papers on Nrf2 were listed in the “Web of Science” database, with more than 1000 new papers published each year. As expected, terms related to oxidative stress and antioxidant molecules occur very often in the Nrf2 literature throughout the years. Interestingly, there is also a gradual increase in the occurrence of terms related to diseases or to natural compounds, the most prominent being sulforaphane, curcumin, and resveratrol that modulate the Nrf2 pathway. Going beyond molecular biology/biochemistry and related fields, Nrf2 research has begun to spread into more clinical areas like endocrinology/metabolism, cardiology, and nephrology, likely reflecting an increased interest in clinical applications of Nrf2 pathway activators. China has become the most prolific producer of Nrf2 papers the last five years followed by the USA and Japan, a reverse pattern compared to the past. In conclusion, Nrf2 is the subject of a globally active research field that keeps growing and extends from bench to bedside.